Forage maize nutritional quality according to organic and inorganic fertilization - Moreno-Reséndez, Alejandro (2017)
The research was conducted on a commercial land plot from the ejido Granada, municipality of Matamoros, Coahuila, situated inside the Comarca Lagunera, from April to August 2015, in order to establish the effect of two fertilization sources – organic and inorganic, upon the nutritional quality of forage maize during the spring-summer cycle with a randomized block experimental design. T1= Acadian soil +Acadian foliage (marine algae extracts) and T2= Regional control, with 16 replications. The evaluated variables were the nutritional quality of forage maize and the milk production (L•t-1 dry matter and L•ha-1). Due to the effect of the evaluated treatments, statistical differences were registered, both for, nutritional values of forage maize, such as: neutral and acid detergent fiber, non-fiber carbohydrates, total digestible nutrients, total net energy for lactation and for milk production, in favor of organic fertilization. Therefore, it can be concluded that fertilizers of marine origin applied to forage maize increased both nutritional quality of forage maize and milk yield per ton of dry matter and per hectare of this forage.